Dubious Versus Trustworthy Faces - What Difference Does it Make for Tax Compliance? - Kai A. Konrad; Tim Lohse; Salmai Qari (Center for Economic Studies and ifo Institute (CESifo), 2013)
We find experimental evidence that the decision problem of tax compliance changes if subjects' declarations are not randomly assessed, but is based on their appearance as captured by pictures of their faces, even if the aggregate audit probability does not change. Some subjects may fear that their picture looks rather dubious whereas others may believe that their picture looks more trustworthy than average. Depending on these beliefs, they may adjust their compliance decisions. Our experimental design allows to disentangle these potentially countervailing effects.
Keywords: H26; C91; H31; 330; compliance; tax evasion; face picture; audit probability